Efficacy and safety of off-label direct oral anticoagulants vs. warfarin for left ventricular thrombus: an inverse probability of treatment weighting analysis - Al-Maimoony, Taha; Al-Matari, Khairallah; Al-Habeet, Abdulhafeedh; Aljaber, Nouradden Noman; Al-Marwala, Mohamad; Al-Hashmi, Salah (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveTo evaluate the efficacy and safety of using off-label direct oral anticoagulants (DOACs) compared to warfarin for treating left ventricular (LV) thrombi using inverse probability-of-treatment weighting (IPTW) analysis.MethodsAn observational study of 302 eligible patients with newly diagnosed LV thrombi was conducted at a tertiary referral center from January 2020 to December 2023. Of the 302 patients, 183 received treatment with DOACs, while 119 were treated with warfarin. The primary endpoint was defined as the complete resolution of the thrombus within one month. The secondary endpoints were defined as the complete resolution of the thrombus within six months along with the following events, including minor and major bleeding events, a systemic embolism, transient ischemic attack, stroke, and all-cause mortality. Alongside individual endpoints, a composite endpoint involving ischemic stroke or mortality was also examined.ResultsIPTW estimates suggested that DOACs were significantly more effective than warfarin in resolving LV thrombus within one month (RR: 1.38; 95% CI: 1.14–1.66; p-value: <0.001). However, there were no significant differences between the two groups in all secondary endpoints, except that DOACs were significantly associated with a lower incidence of the composite outcome of ischemic stroke and all-cause mortality (RR: 0.96; 95% CI: 0.93–0.99; p-value: 0.040). In DOAC subgroup analysis, only rivaroxaban demonstrated earlier and superior resolution of LV thrombus with non-inferior safety when compared to warfarin.ConclusionsDOACs, specifically rivaroxaban, could be a promising therapeutic alternative for treating LV thrombi. Further research through randomized clinical trials is necessary to confirm our findings.